Artificial Intelligence Use in the Issuance of Inheritance Fatwas: Evaluating GPT-3.5 Compliance with Islamic Legal Principles - Manswab Mahsen Abdulrahman; Abdul Hafiz Musa Walusimbi (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Abstract: The aim of this study was to evaluate the compliance of GPT-3.5 to Islamic legal principles in issuing fatwas on inheritance distribution. The focus was on the economic impact of artificial intelligence (AI) on social welfare development and comparison with the potential of GPT-3. Qualitative and mixed methods were used to collect data from different sources, including books, journal articles, reports, conference papers, and jurisprudence academies. A comprehensive analysis was conducted on the significance of fatwas, their historical development, traditional methods, and the role of technology, including AI and natural language processing, within the Islamic context. Moreover, data were collected on inheritance cases associated with issues such as murder, religious differences, heirs of the Qur'an, residual heirs, distant relatives, exceptions, al-Minbariyyah, al-Radd, al-Umariyyah, al-Akdariyyah, missing persons, and multiple deaths. The findings showed that the ability of GPT-3.5 to issue fatwas was consistent with the principles of Islamic law as well as its potential to offer faster response times compared to traditional methods. However, GPT-3.5 showed inconsistencies, specifically in issuing fatwas related to inheritance distribution in cases related to murder, religious differences, heirs of the Qur'an, remaining heirs, distant relatives, exceptions, al-Minbariyyah, al-Radd, al-Umariyyah, and al-Akdariyyah. This study contributes to the law and policymaking in global Muslim countries with a focus on the proper and correct use of technology in Islamic law issues in the contemporary era.